The Interplay Between Diet Quality and Pre-pregnancy Body Mass Index on Glycemic Parameters in Pregnancy: A Comparison of Various Diet Quality Scores (OR35-02-19). (13th June 2019) - Lindsay, Karen; Buss, Claudia; Entringer, Sonja; Wadhwa, Pathik
Abstract: Objectives: Nutrition in pregnancy plays an important role in maintaining glycemic control but there is no consensus on how to characterize maternal diet quality with respect to glycemic outcomes. The objective of this study is to compare the associations between 4 indices of diet quality with biomarkers of glycemic control (insulin, homeostasis model of insulin resistance (HOMA-IR)) in pregnancy, and to determine whether associations vary as a function of pre-pregnancy body mass index (pBMI). Methods: In a prospective longitudinal study of N = 220 pregnant women, dietary intakes were assessed at 3 time points across gestation by 3 × 24h-diet recalls per assessment, from which 4 validated diet quality scores were derived: Dietary Approaches to Stop Hypertension (DASH), Alternative Healthy Eating Index for Pregnancy (AHEI-P), Mediterranean Diet Score (MDS), Dietary Inflammatory Index (DII). Fasting blood samples collected at each assessment were assayed for insulin and glucose and HOMA-IR was computed. pBMI was computed from self-reported pre-pregnancy weight and measured height. Linear regression models predicting mean pregnancy values of insulin and HOMA-IR by diet quality score and pBMI and the diet quality*pBMI interaction term were computed. Results: pBMI is strongly predictive of insulin and HOMA-IR and each diet quality score exerts similar significant main effects on glycemic parameters (Table 1). Only the DII * pBMI interaction term was significantly associated with insulin and HOMA-IR (Table 2). Figures 1A and 1B depict that the effect of DII on glycemic control is most pronounced for women with a pBMI < 25.0 Kg/m2, while levels among overweight and obese women remain relatively stable regardless of the inflammatory profile of the diet. Neither DASH, MDS or AHEI-P showed a significant effect on glycemic markers when analyzed as a function of pBMI. Conclusions: Although each of the examined diet quality scores may serve as crude predictors of glycemic control in pregnancy, only the DII detected significant differential effects as a function of pBMI. A more pro-inflammatory diet in normal weight pregnant women may exert a stronger influence on glycemic control compared to overweight and obese women, likely attributed to the overriding effects of excess adiposity on dysglycemia. Funding Sources: National Institutes of Health: NICHD, NIMHD, NIMH. Supporting Tables, Images and/or Graphs: